Simultaneous measurement of the mission quantum yield and local temperature: The illustrative example of SrF2:Yb3+/Er3+ Single Crystale - Brites, Carlos D. S. (2020)
The emission quantum yield is one of the key figures of merit to evaluate the photoluminescence performance of luminescent materials. The emission quantum yield of upconverting materials is still not widely reported due to technical difficulties and intricate dependence on the excitation power density that is mirrored in a temperature increase. This work describes the simultaneous determination of the emission quantum yield (for both downshifting and upconverting processes) and of the temperature by using the output of a commercial integrating sphere. The temperature is calculated by primary luminescence thermometry through the Boltzmann equation, analyzing the intensity ratio between the 2H11/2, 4S3/2→4I15/2 transitions. The procedure is illustrated using of SrF2: Yb3+/Er3+ single crystals with distinct Yb3+ compositions and the effect of the Yb3+ content on the emission quantum yield and the temperature increase of the sample.